Isotope analysis for understanding mountain springs in western Nepal - Bharati, Luna; Khadka, Ambika; Kumar, Sudhir; Dhaubanjar, Sanita; Drown, Patrick (International Water Management Institute, 2019)
Springs are a major source of water in the hills and mountains of Nepal. Since 2014, with funding from the Asian Development Bank and the Nordic Development Fund, the “Building Climate Resilience of Watersheds in Mountain Eco-Regions” (BCRWME) project is working to provide 45,000 households in vulnerable mountain communities with access to more reliable water resources via spring or surface water sources. Despite the recognition of springs as a livelihood driver in these communities and the observed alarming trends in the drying up of springs, a scientific understanding of mountain springs in Nepal has not been established. Under BCRWME, the International Water Management Institute (IWMI) is leading comprehensive research into characterizing mountain springs and identifying science-based interventions that can increase reliability and water availability in these sources. IWMI is conducting isotope analysis to investigate hydrological processes in mountain springs and identifying recharge zones in order to sustain springs in Banlek and Shikarpur in western Nepal.